2017
DOI: 10.3329/bjz.v45i1.34190
|View full text |Cite
|
Sign up to set email alerts
|

Fish species diversity, fishing gears and crafts from the Buriganga river, Dhaka

Abstract: Fish species, fishing gear and crafts in the most polluted river Buriganga were inventorial. During December, 2012 to November, 2013, a total of 56 fish species belonging to 20 families and 9 orders were recorded. Cypriniformes observed to be the most dominant order with 18 species (32%). The highest fish diversity was recorded during monsoon season, and lowest during winter. Maximum diversity variance (7.616 ± 2.76 Sd) observed in the monsoon season for 56 species (220 individuals). Also 12 different types of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
5
1
Order By: Relevance
“…Although a study on fish passage between the Jamuna and Bangali rivers recorded a total of 69 fish species under 9 orders and 26 families by using different types of fine nets, that is a little bit more than in our study (Zaman and Naser, 2019). Previously, Bhuiyan (1964) concluded a survey on the River Buriganga in Dhaka by recording a total of 71 freshwater fish species under 25 families and 45 genera from the river, but in recent years Baki et al (2017) reported a total of 56 fish species belonging to 20 families and 9 orders from the same river.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Although a study on fish passage between the Jamuna and Bangali rivers recorded a total of 69 fish species under 9 orders and 26 families by using different types of fine nets, that is a little bit more than in our study (Zaman and Naser, 2019). Previously, Bhuiyan (1964) concluded a survey on the River Buriganga in Dhaka by recording a total of 71 freshwater fish species under 25 families and 45 genera from the river, but in recent years Baki et al (2017) reported a total of 56 fish species belonging to 20 families and 9 orders from the same river.…”
Section: Discussioncontrasting
confidence: 55%
“…The water quality of the river has been deteriorating due to intensive human intervention, unplanned urbanization, rapid industrialization and population pressure around the river (Sarker, 2005;Moniruzzaman et al, 2009;Nouri et al, 2009). The large input of organic matter to aquatic flood plain habitats may reduce the amont of dissolved oxygen which results in the emigration or reduction of a great number of fish in the river (Winemiller, 1989;Baki et al, 2017). Threats from these types of human intervention might be a potential reason for species reduction in the River Buriganga.…”
Section: Discussionmentioning
confidence: 99%
“…It was mentioned that these changes may result in the intrusion of seawater into the lake, leading to an increase in the lake's salinity (Eid & Shaltout, 2013;Shalby et al, 2020;Ouda, 2022). Therefore, understanding the taxonomic composition is critical for sustainable water bodies management (Baki et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…This river is of paramount importance as the main drainage channel of Dhaka city (Salam and Alam, 2014) and is of great importance from an economic point of view (Ahmed and Bodrud-Doza, 2013). The Turag is also home to a substantial amount of human activity ranging from navigation (Rahman et al, 2013), fishing (Baki et al, 2015), agriculture (World Bank, 2007), and in many instances, as a source of water for domestic purposes (Bhuiyan et al, 2011). Considering the sources of drinking water and the proportion of households adjacent to the Turag River, twelve areas, namely Konabari, Kashimpur, Ichharkandi, Palasana, Gutia, Gusulia, Bhakral, Bhadam, Rashadia, Kathaldia, Abdullahpur, and Mausaid (Map 1) were selected for the survey.…”
Section: Selection Of Study Area and Populationmentioning
confidence: 99%